[OA211] A single phantom, a single statistical method, a single figure of merit for all X-ray equipment. (August 2018) - Paruccini, Nicoletta; Villa, Raffaele; Oberhofer, Nadia; Loria, Alessandro; Signoriello, Michele; Crespi, Andrea
Abstract : Purpose: The aim of this study is to collect Statistical Low Contrast Detectability Threshold (LCth ) data from different equipment using the same phantom and the same software for the analysis. All data will be expressed with same unit, that is mmAl. Equipment types include: Digital radiography (DR), Computed Radiography (CR), 2D Digital Mammography, Tomosynthesis and Syntetic 2D Mammography, Fluoroscopy, Fluorography and Digital Subtracted Angiography (DSA) from Angiography. Data from this study will define the reference value and the tolerance for quality control tests. Methods and materials: A phantom consisting of a square aluminium target and a 5-step-wedge (0.25–1.25 mmAl) was built. A Matlab software automatically calculates LCth values in terms of Pixel Value (PV) and it also converts PV to mmAl, providing the LCth (mmAl). Standard setting used for different modality: RQA5 beam at 2.5 μGy kerma entrance at the detector for DR and CR; automatic acquisition with 16 cm of PMMA filtration for angiography and 5 cm PMMA phantom for mammography setting. The images analysed in this study are both processed and unprocessed. Results: This method is able to collect low contrast detectability information from different modalities and equipment by different vendors. Preliminary results are summarized by detail. For example, for 0.5 mm diameter detail results in the range of: 0.05–0.08, 0.04–0.093, 0.018–0.023, 0.26–0.3 and 0.36–0.41 mmAl LCth for tomosynthesis images, synthetic 2D, 2D mammography, DR and CR images, respectively. Furthermore, from the intercomparison activity of AIFM working group on angiographic equipment, for 2.5 mm diameter detail, results have been derived in the range of: 0.35–0.88, 0.31–0.58, 0.35–0.49, 0.046–0.59 LCth expressed in mmAl unit for low dose and normal dose fluoroscopy, coronary fluorography, cerebral DSA, respectively. Conclusion: The Low Contrast Detectability phantom and statistical method can be easily implemented for all modalities. Data from this study can be used to define the reference value and the tolerance for low contrast threshold quality control in digital radiography.